Trace Evidence Potential in Postmortem Skin Microbiomes: From Death Scene to Morgue12. Issue 3 (8th November 2018) - Kodama, Whitney A.; Xu, Zhenjiang; Metcalf, Jessica L.; Song, Se Jin; Harrison, Nicholas; Knight, Rob; Carter, David O.; Happy, Christopher B.
Abstract: Microbes can be used effectively as trace evidence, at least in research settings. However, it is unknown whether skin microbiomes change prior to autopsy and, if so, whether these changes interfere with linking objects to decedents. The current study included microbiomes from 16 scenes of death in the City and County of Honolulu and tested whether objects at the scenes can be linked to individual decedents. Postmortem skin microbiomes were stable during repeated sampling up to 60 h postmortem and were similar to microbiomes of an antemortem population. Objects could be traced to decedents approximately 75% of the time, with smoking pipes and medical devices being especially accurate (100% match), house and car keys being poor (0%), and other objects like phones intermediate (~80%). These results show that microbes from objects at death scenes can be matched to individual decedents, opening up a new method of establishing associations and identifications.